Morphometric Study of Body of Lumbar Vertebrae: MRI Study - Tenginkai, Poonam; Nakhate, Manisha; Yadav, Dipin Kumar (Journal of Neonatal Surgery, 2025)
Introduction- A typical vertebra has a ventral body; a dorsal vertebral (neural) arch, extended by lever-like processes; and a vertebral foramen, which is occupied in life by the spinal cord, meninges, and vessels. Fibrocartilage intervertebral discs connect opposing surfaces of neighboring bodies. Supporting the entire weight of the head and trunk, the entire column of bodies and discs creates the body's sturdy yet flexible central axis. Additionally, it transfers much stronger forces produced by muscles that are either directly or indirectly linked to it. In addition to forming a vertebral canal for the spinal cord, intervertebral foramina also carry mixed spinal nerves, smaller recurrent nerves, and blood and lymphatic vessels between adjacent neural arches, close to their connections with vertebral bodies. Material and methods- A retrospective evaluation of the morphometric parameters of the lumbar vertebrae was conducted on 150 patients with lower back pain aged 25 to 75 years in the Department of Anatomy D Y Patil Medical College in collaboration with the Radiology Department of D Y Patil Hospital, Nerul, Navi Mumbai. Obtained patients data were separated in 6 groups, in the basis of patients ages, Group A (25-30 years), Group B (31-40 years), Group C (41-50 years), Group D (51-60 years), Group E (61-70 years) and Group F (71-75 years). Morphometric parameters of 1-5 Lumbar vertebrae were recorded with MRI. Result- In the present study, the age of the patients ranged from 25 to 75 years old. The mean value and standard deviation of the age of patients were 48.586±13.208. The average anteroposterior diameter was 25.26±3.97, 26.81±3.15, 27.76±3.05, 28.31±3.02, and 28.72±3.95 mm at L1, L2, L3, L4, and L5 of lumbar vertebrae, respectively. The average transverse diameter of lumbar vertebrae was 34.53±5.97, 36.88±6.08, 40.62±5.29, 42.64±4.85 and 43.87±7.82 mm at L1, L2, L3, L4, and L5 of lumbar vertebrae respectively. The average vertical diameter of lumbar vertebrae was 20.54±1.88, 21.8±2.42, 22.09±2.42, 21.81±2.66, and 22.39±3.24 mm at L1, L2, L3, L4, and L5 of lumbar vertebrae respectively. Conclusion: This study revealed a significant correlation between the body of lumbar vertebrae and the patient's age